Penerapan Metode Certainty Factor Dalam Diagnosa Hermatologi-Onkologi - Nur Yanti Lumban Gaol; Lusiyanti Lusiyanti; Asyahri Hadi Nasyuha (STMIK Budi Darma, 2022)
Hematology oncology is a blood cancer that is quite worrying because it is identical to a condition that leads to death and this happens all over the world, where this disease not only affects adults but can also occur in children. Some experts suspect that the cause of blood cancer is due to changes in DNA that can trigger healthy blood cells to become cancerous. The World Health Organization (WHO) has stated that blood cancer is a very serious health problem because the number of sufferers increases by about 20% per year. This condition can certainly be prevented if patients who experience this disease can be detected early. To help overcome these problems, an Android-based system was developed that can diagnose blood cancer early based on the symptoms experienced by the patient, and this system was developed through a process of adopting expertise from experts into the form of a computer-based system known as the Expert System. . In order for the results of the diagnosis to have a high level of accuracy, an appropriate method is needed in its application, for that a method with a certainty factor algorithm is used. Based on the research results, in designing an expert system that adopts the Certainty Factor method, it can be used in solving problems related to the process of diagnosing hematological oncology diseases with an accurate level of certainty, this makes the diagnosis process easier and accuracy in determining oncological hematological diseases by utilizing the system.